2014
DOI: 10.1155/2014/702683
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Linguistic Appropriateness and Cultural Sensitivity of a Self-Report System for Spanish-Speaking Patients with Cancer

Abstract: Spanish speakers in the United States encounter numerous communication barriers during cancer treatment. Communication-focused interventions may help Spanish speakers communicate better with healthcare providers and manage symptoms and quality of life issues (SQOL). For this study, we developed a Spanish version of the electronic self-report assessment for cancer (ESRA-C), a web-based program that helps people with cancer report, track, and manage cancer-related SQOL. Four methods were used to evaluate the Spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Cultural sensitivity was assessed using the Cultural Sensitivity Assessment Tool (CSAT), which was originally developed to assess cultural sensitivity of printed cancer materials for AAs ( Guidry & Walker, 1999 ), and has since been used to evaluate cancer educational materials for diverse racial/ethnic groups ( Friedman & Hoffman-Goetz, 2006a ; Friedman & Kao, 2008 ; Thomson & Hoffman-Goetz, 2007 ; Tofthagen et al, 2014 ). Three categories of CSAT—format (3 items), written message (11 items), and visual message (16 items)—were assessed using a 4-point Likert scale (4 = strongly agree ; 3 = agree ; 2 = disagree ; 1 = strongly disagree ).…”
Section: Methodsmentioning
confidence: 99%
“…Cultural sensitivity was assessed using the Cultural Sensitivity Assessment Tool (CSAT), which was originally developed to assess cultural sensitivity of printed cancer materials for AAs ( Guidry & Walker, 1999 ), and has since been used to evaluate cancer educational materials for diverse racial/ethnic groups ( Friedman & Hoffman-Goetz, 2006a ; Friedman & Kao, 2008 ; Thomson & Hoffman-Goetz, 2007 ; Tofthagen et al, 2014 ). Three categories of CSAT—format (3 items), written message (11 items), and visual message (16 items)—were assessed using a 4-point Likert scale (4 = strongly agree ; 3 = agree ; 2 = disagree ; 1 = strongly disagree ).…”
Section: Methodsmentioning
confidence: 99%
“…Non-English speaking HLs may experience challenges engaging with healthcare professionals due to the language barrier as many providers are English monolingual 88 . Despite efforts to use medical interpreters, patient navigators or promotoras, these challenges persist and may lead to an inadequate patient understanding of illness and a barrier to engaging further with healthcare providers 89,90 .…”
Section: Addressing Disparities Through Cultural Sensitivity and Commmentioning
confidence: 99%
“…With a better understanding of their disease, treatment algorithms, and prognoses, HL can then make informed decisions about their care and feel empowered to guide their own treatment, helping to overcome the large disparities often present. The benefits afforded by pairing a patient with a member of their ethnic background may be partially due to alleviating language barriers, but studies have shown that additional cultural factors help to improve patient comfort as well [88]. Hispanics and Latinos identify more with health care providers of similar cultures, family beliefs, and religions because of a bond formed through shared experiences [140].…”
Section: Call To Action: Recommendations For Achieving Health Equitymentioning
confidence: 99%